How does public infrastructure construction influence CO2 emissions? A global case - Qian, Yichen; Sun, Renjin; Zhao, Jun; Song, Sasa; Wang, Pinchen (Frontiers in Environmental Science, 2022)
To empirically investigate as to whether and how public infrastructure influences the global greenhouse effect, this study utilizes a panel dataset of 35 countries over the period 2003-2019 for regression estimation. Furthermore, regional heterogeneous and mediation effects between infrastructure and carbon dioxide (CO2) emissions are explored. The primary findings insist that: (i) at the global level, public infrastructure is positive associated with CO2 emissions. In other words, strengthening infrastructure at this stage is not conducive to mitigating the greenhouse effect; (ii) public infrastructure construction development in Belt and Road Initiative (BRI) countries has a greater positive impact on CO2 emissions than in non-BRI countries; and (iii) the mediation roles of industrial upgrading and trade openness are established; specifically, trade openness and industrial upgrading are valid transmission routes through which public infrastructure affects CO2 emissions. Based on the above three findings, a number of policy implications related to accelerate low-carbon construction of infrastructure and promote industrial upgrading are proposed.